EFEKTIVITAS KOMPOSISI TRIPLE THERAPY TERHADAP DISPEPSIA DENGAN INFEKSI HELICOBACTER PYLORI: Tinjauan Systematic Review - Theodora Putri Simanjaya (2022)
Dyspepsia is a disease with one or more symptoms relating to abnormalities in gastroduodenal. One of the factor that influence dyspepsia is Helicobacter pylori (H. pylori). Clarithromycin-based triple therapy is recommended as first line eradication treatment. Resistence towards clarithromycin is increasing and causing eradication rates in Clarithromycin-based triple therapy to decrease. The purpose of this study was to determine the effectivity of triple therapy variation on dyspepsia with H. pylori infection. Data was collected through literature searches on two different databases using the preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) 2020. This systematic review included all relevant articles from 2011-2021. Six studies met the inclusion criteria. The results showed that metronidazole-based triple therapy is effective in eradicating H. pylori due to its eradication rate surpassing the target rate of 80%. The highest eradication rates in intention-to-treat (ITT) and per-protocol (PP) were 94.3% and 93.5%, respectively. The best triple therapy composition is metronidazole-based triple therapy with 7 days of duration.